(untitled) (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1953)
The author present a case of false traumatic hernia on the left flank of a dog, the great omentum and spleen being found as the contents. After referring the cases recorded in the available literature, they describe the clinical observation and the performance of the operation, including the post-operative period. They comment on the diversity of opinions concerning the term "hernia", specially analyzing the point of view of IGARZABAL. They examine the various conceits given by veterinary pathologists about the so-called ventral hernias, hernia of the "linca alba" and of the flank. Finally, the conclude upon the rarity of this affection in the dog.